Estratégias de textualização em redações de vestibular - Noronha, Vanessia Pereira (2017)
The construction of texts based on the interaction and on the learning of textualization strategies allows the understanding of the importance of certain factors involved in reading and writing. In this work, we analyze the construction of textualization strategies in essays of university entrance tests from 2015 and 2016, written by the applicants to the course of Letters of the Federal University of Roraima, in its four majors, which are Literature, English, Spanish and French. This study aimed to show, through the analysis of the corpus, the use of these strategies in the textual scope, as well as the effects produced by them in the construction of the meaning of the text. As a basis for our research, we adopted as theoretical assumptions the grounds of Text Linguistics, through the studies by Koch (2002; 2004; 2009; 2015), Marcuschi (1983; 1998; 2005; 2007), Costa Val (1999, 2004) and Fávero (1986;2006). The framework is also anchored in the theoretical and methodological framework of Sociodiscursive Interactionism, proposed by Bronkart (1999; 2008). This dissertation has a bibliographical and analytical methodological orientation. It was carried out in two steps: in the first one, we discussed the theory on the grounds proposed by Text Linguistics and the conceptions of Sociodiscursive Interactionism. In the second one, we analyzed eight previously chosen essays for the research based on the object of study established. The research revealed that, in most of the essays, the applicants explored their previous knowledge and employed textualization strategies appropriately and significantly to the development of writing, thus, favoring the applicants’ textual construction.